Investigations into data published and consumed on the Web: a systematic mapping study - Santos, Helton Douglas A. dos; Oliveira, Marcelo Iury S.; Lima, Glória de Fátima A. B.; da Silva, Karina Moura; S. Muniz, Rayelle I. Vera Cruz; Lóscio, Bernadette Farias (Journal of the Brazilian Computer Society, 2018)
The increasing interest in using the Web as a platform for data sharing has motivated research about publishing and consuming data on the Web. While this subject is gaining importance, up until now, there are not many academic papers reviewing the approaches for publishing and consuming data on the Web. Furthermore, to the best of our knowledge, there is no systematic review of the literature that analyzes this subject. In this article, we conduct a systematic mapping study that aims to provide an overview of the current literature on publishing and consuming data on the Web by conducting a systematic mapping study. This study seeks to function as a snapshot of this subject by (i) identifying and analyzing how data have been published and consumed on the Web, (ii) discovering the benefits and limitations of publishing and consuming data on the Web (iii) analyzing the evolution of research on publishing and consuming data on the Web, and (iv) classifying the studies into categories related to their contribution. Finally, we discuss the results of this study and their implications for research on data on the Web-related subjects.